Pelatihan Penulisan Puisi untuk Meningkatkan Keterampilan Pemilihan Kosakata Siswa MA Muhammadiyah Unggulan Kota Gorontalo - Egam, Ahmad Syahdan; Y. Rahman, Nurjuliati Salsabila; Zakaria, Ulfa (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to improve the vocabulary selection skills (diction) of students at MA Muhammadiyah Unggulan Kota Gorontalo through poetry writing training. The identified problems were students' low vocabulary mastery and difficulties in choosing the right words to express ideas poetically. The implementation method used a participatory approach with stages: material provision, poetry appreciation and analysis, vocabulary exploration and enrichment, guided writing practice, discussion and feedback, and work publication. The results showed that before the training, students' vocabulary selection skills were in the poor category, marked by the use of literal and cliché words. After participating in training focused on vocabulary enrichment and diction selection, there was a significant improvement manifested in the quality of the poetry produced. The peak of this activity's success was the publication of a student poetry anthology book entitled "Ruang, Waktu, dan Kehidupanku" which became concrete evidence of the improvement in participants' vocabulary selection skills.